ANALISIS VARIABEL ROE, EPS, PER, SENSITIVITAS KURS, SENSITIVITAS INFLASI, SENSITIVITAS SUKU BUNGA DAN PENGARUHNYA TERHADAP HARGA SAHAM PERUSAHAAN: (Studi Pada Perusahaan yang Masuk dalam Indeks LQ45 Periode 2010-2013) - Suselo, Dedi (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2016)
The research aims to investigate the influence of ROE, EPS, PER, the sensitivity of exchange rate, the sensitivity of inflation, and the sensitivity of interest rate variables on stock prices in the LQ45 index time period 2010 to 2013. Population of the research are 45 companies in the LQ45 index. The analysis method of the research is multiple regression linier. The results of the research indicated that ROE, EPS, PER, the sensitivity of exchange rate, and the sensitivity of inflation has significant positive effect on stock prices. The sensitivity of interest rate has significant negative effect on stock prices. The research contributed to the development of the sciene of management and investment, especially the influence of ROE, EPS, PER, the sensitivity of exchange rate, the sensitivity of inflation, and the sensitivity of interest rate variables on stock prices. Keywords: ROE, EPS, PER, The Sensitivity of Exchange Rate, The Sensitivity of Inflation, The Sensitivity of Interest Rate